Eco-Friendly Photocatalyst from Limestone: ZnO-Hydroxyapatite Composite for Efficient Rhodamine B Removal - Sukarta, I Nyoman; Suyasa, I Wayan Budiarsa; Mahardika, I Gede; Suprihatin, Iryanti Eka; Sastrawidana, I Dewa Ketut; Wiratma, I Gusti Lanang; Darmayasa, Dewa Komang (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
This study aims to synthesize and characterize a limestone-based ZnO-hydroxyapatite (HA/ZnO) composite and evaluate its performance in the photocatalytic degradation of Rhodamine B under UV irradiation. Hydroxyapatite was synthesized by reacting calcined CaO from limestone with orthophosphoric acid and subsequently combined with ZnO via a co-precipitation–hydrothermal method. The materials were characterized using X-ray Diffraction (XRD) and Fourier Transform Infra Red (FTIR) to determine their crystal structure and functional groups. The HA/ZnO composite exhibited the smallest crystallite size (14.86 nm), indicating enhanced surface area and strong interfacial interaction. Photodegradation tests revealed optimal conditions at pH of 9, Rhodamine B concentration of 20 mg/L, and catalyst dosage of 1.5 g, achieving a maximum degradation efficiency of 99.81%. Toxicity assessment using a corn seed germination test showed a significant increase in germination rate from 16% (untreated) to 92% (after photocatalytic treatment). These findings suggest that the limestone-derived HA/ZnO composite is a promising, environmentally friendly, and efficient photocatalyst for textile dye wastewater treatment. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).